Investigation of multilayer thin films using ellipsometry - He, Lining. (2009)
Spectroscopic Ellipsometry (SE) is a powerful and universal optical technique for the investigation of optical properties of semiconductor thin films. It is an extremely sensitive measurement tool for the characterization of single layer thin film and even multilayer structures. This project focuses on the study of optical properties of amorphous silicon rich nitride (a-SRN) in single bulk layer and in multilayer by SE fitting using software Wvase32. SE itself is not a direct readout type technique. It is actually a model-based technique. Thus, it is important to build correct and suitable model for a particular material in the SE fitting. In this project, several dispersion models are investigated to find the one which is best suitable for the fitting of a-SRN. Those dispersion models include Cauchy urbach model, Lorentz oscillator model, Forouhi & Bloomer’s model, Cauchy absorption model and Tauc-Lorentz model. Furthermore, the optical properties of a-SRN in single bulk layer with different SiH4/NH3 ratio have been studied by SE fitting using Tauc-Lorentz model. It is clearly shown that the bandgap of a-SRN will decrease and optical constants (n & k) will increase with increasing SiH4/NH3 ratio. Finally, the SE fitting of four a-SRN quantum well multilayer samples has been conducted. Two samples consist of 45 alternating layers of a-SRN well and SiO2 barrier. Another two consist of 40 alternating layers of a-SRN well and Si3N4 barrier. The optical properties of these samples have been studied in detail using SE and photoluminescence (PL). It is observed that the SE fitting for multilayer samples are much more challenging than single bulk layer due to their structure complexity. The multilayer samples after annealing have also been studied. A second peak emerges in the PL spectra of the annealed samples, which may be attributed to the formation of Si nanocrystals in the well layers.